2020
DOI: 10.1038/s41612-020-00143-w
|View full text |Cite|
|
Sign up to set email alerts
|

Low Antarctic continental climate sensitivity due to high ice sheet orography

Abstract: The Antarctic continent has not warmed in the last seven decades, despite a monotonic increase in the atmospheric concentration of greenhouse gases. In this paper, we investigate whether the high orography of the Antarctic ice sheet (AIS) has helped delay warming over the continent. To that end, we contrast the Antarctic climate response to CO2-doubling with present-day orography to the response with a flattened AIS. To corroborate our findings, we perform this exercise with two different climate models. We fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Firstly, Southern Ocean is the crucial factor for the huge accumulated ocean heat uptake 7 . Secondly, the high elevation of Antarctica plays an important role in decreasing the susceptibility to CO 2 -forced warming 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, Southern Ocean is the crucial factor for the huge accumulated ocean heat uptake 7 . Secondly, the high elevation of Antarctica plays an important role in decreasing the susceptibility to CO 2 -forced warming 67 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study [20] also infers that the Tibetan Plateau below 5 km exhibit EDW; it did not show any EDW above 5 km or in future climate projections. A study [65] demonstrated Antarctic exhibits low elevation warming in response to 2 × CO 2 forcing. Additionally, this past-future linkage concludes that elevation-dependent temperature changes strongly depend on the geographical orientation of mountains rather than CO 2 concentration.…”
Section: Partial Contributions From Radiative and Non-radiative Feedbackmentioning
confidence: 99%
“…Antarctica is warming at slightly more than half the rate of the planet (0.56 times), largely due to high ice sheet orography (Singh & Polyani, 2020), weaker Antarctic surface albedo feedback, ocean heat uptake in the Southern Ocean, Antarctic ozone depletion (Masson-Delmotte et al, 2013), and varying Antarctic surface heights (Salzmann, 2017). There is also significant inter-annual variation, begetting a low coefficient of determination with respect to the Antarctic 60-month moving average.…”
Section: Observational Analysismentioning
confidence: 99%